2014
DOI: 10.1080/00207721.2014.919073
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent estimation of efficiency, effectiveness and returns to scale

Abstract: In recent years, data envelopment analysis (DEA) has been widely used to assess both efficiency and effectiveness. Accurate measurement of overall performance is a product of concurrent consideration of these measures. There are a couple of well-known methods to assess both efficiency and effectiveness. However, some issues can be found in previous methods. The issues include non-linearity problem, paradoxical improvement solutions, efficiency and effectiveness evaluation in two independent environments: divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A data envelopment analysis (DEAs) is a data-oriented technique proposed by Charnes et al (1978). It was developed for measuring the relative efficiencies within a group of decisionmaking units (DMUs) that utilize some inputs to generate a set of outputs (Dobos and V€ or€ osmarty, 2019;Hilmola et al, 2015;Khodakarami et al, 2016;Lin and Chen, 2017;Yu and Hsiao, 2018;Seydel, 2006). A data envelopment analysis can identify the strengths and weaknesses of each industrial unit based on industry criteria.…”
Section: Data Envelopment Analysismentioning
confidence: 99%
“…A data envelopment analysis (DEAs) is a data-oriented technique proposed by Charnes et al (1978). It was developed for measuring the relative efficiencies within a group of decisionmaking units (DMUs) that utilize some inputs to generate a set of outputs (Dobos and V€ or€ osmarty, 2019;Hilmola et al, 2015;Khodakarami et al, 2016;Lin and Chen, 2017;Yu and Hsiao, 2018;Seydel, 2006). A data envelopment analysis can identify the strengths and weaknesses of each industrial unit based on industry criteria.…”
Section: Data Envelopment Analysismentioning
confidence: 99%
“…Tis method is able to evaluate returns to scale to the right and left of the given unit in all conditions. In the same vein, Khodakarami et al [37] in their article "concurrent estimation of efciency, efectiveness, and returns to scale" studied the efciency, efectiveness, and return to scale of DMUs simultaneously. Machado et al [38] research the hypothesis that economies of scale are a typical feature of the generation market in Brazil used by the cost structure of the electricity generation companies by using a translog cost function in Brazil during the period 2000-2010.…”
Section: Introductionmentioning
confidence: 99%
“…Well-known methods for measuring productivity by assessing efficiency and effectiveness are available in literature: Network DEA (Cook et al , 2010), integrated two-stage DEA (Chen et al , 2009), ICCR (integrated Charnes et al , 1978) and IBCC (integrated Banker et al , 1984) models (Chiou et al , 2010), and classic DEA models (Chiou and Chen, 2006; Karlaftis, 2004). According to Khodakarami et al (2016), critical points can be found in those studies. Arguments include problem of non-linearity, suggesting paradoxical improvement strategies, evaluating efficiency and effectiveness in two independent environments, dividing a decision-making unit (DMU) into two autonomous departments for performance evaluation, and problems associated with determining economies of scale.…”
Section: Introductionmentioning
confidence: 99%
“…Arguments include problem of non-linearity, suggesting paradoxical improvement strategies, evaluating efficiency and effectiveness in two independent environments, dividing a decision-making unit (DMU) into two autonomous departments for performance evaluation, and problems associated with determining economies of scale. With respect to the mentioned challenges, Khodakarami et al (2016) defined a number of properties as important features of DEA-based productivity assessment and developed a series of linear DEA methods to estimate efficiency, effectiveness, and returns to scale of DMUs, simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation